Interconversion of Purine Mononucleotides in Pasteurella pestis - Brubaker, R. R. (1970)
Included among the five established determinants of virulence in Pasteurella pestis are the abilities of cells to accomplish the de novo biosynthesis of purines and to grow as dark pigmented (P(+)) colonies on a solid synthetic medium containing hemin. P(+) isolates of P. pestis strain KIM-10 (mouse intraperitoneal ld(50) < 10 cells) failed to convert exogenous guanine-8-(14)C to adenine residues of ribonucleic acid (RNA) when cultivated in a minimal medium which favored the pigmentation reaction. This conversion occurred in P(+) cells grown in an enriched medium which did not support the pigmentation reaction and was observed in P(−) mutants cultivated in both types of media. Both P(+) and P(−) isolates converted exogenous adenine-8-(14)C but not adenine-2-(14)C at a significant rate to guanosine residues of RNA when grown under a variety of conditions. This difference appeared to reflect a deficiency of adenine deaminase. The mouse intraperitoneal ld(50) of purine-auxotrophs was about 10(2) cells when the metabolic block occurred prior to the de novo formation of inosine monophosphate (IMP). In contrast, the corresponding value for a mutant blocked between IMP and guanine monophosphate was > 10(7) cells in mice and > 10(8) cells in guinea pigs.